Macrófitas aquáticas na área de transição entre o rio Areias e o reservatório da Usina Hidrelétrica Luís Eduardo Magalhães - Tocantins: cobertura, biomassa e macroinvertebrados associados - Rodrigues, Úria Graziela Barroso de Souza (Universidade Federal do Tocantins, 2017)
The reservoirs are lentic aquatic environments of easy colonization by aquatic macrophytes, determining species in the structural dynamics of aquatic ecosystems. The cover and the seasonal variation of the biomass of macrophytes species were carried out in the transition stretch between the reservoir of the Luis Eduardo Magalhaes - Tocantins Hydroelectric Power Plant and the tributary river Areias, in order to relate these variables to abiotic factors and interspecific behavior of these vegetables. The collections were quarterly, comprising January to October 2016, and 10 sample points were marked with 3 replicates. Absolute frequency, relative frequency, relative coverage, Bray-Curtis similarity, biomass and abiotic variables (rainfall, temperature, oxygen, transparency, depth and pH) were analyzed. Ten species were sampled, distributed in six families. The most frequent species were Najas microcarpa, Oxycaryum cubense and those with the highest biomass were Oxycaryum cubense and Eichhornia azurea. Salvinia auriculata was more frequent in the rainy season. The results showed that the richness (S = 10) and the diversity (H '= 1.73) of macrophytes were higher in the rainy season, while the biomass was higher in the dry period. The results showed a stability of the reservoir and the predominance of few species coexisting in the environment.